Design of a Blockchain Technology Competence Model for Interdisciplinary Curricula Development - Fomin, Vladislav; Gürpinar, Tan; Balevičienė, Dovilė (Information & Media, 2024)
Contribution. This study identifies blockchain-related competences essential for professionals involved in blockchain projects and develops a blockchain technology competence model for interdisciplinary curricula development. Background. Amidst the surge in blockchain implementations, a gap exists in systematic knowledge about the skills required from blockchain professionals. While the number of new blockchain implementation cases is growing, there are no systematic reviews on the success factors or the skills required from blockchain professionals. Lack of systematic information on blockchain projects and their implementers presents a substantial obstacle to the development of new competence-oriented academic and professional educational programs, as well as for guiding recruitment for blockchain projects. Research Question. This research investigates the necessary knowledge and skills to leverage opportunities and adapt to changing employment trends in blockchain technology. The guiding research question of this study is, what knowledge and skills must be acquired in order to be able to exploit opportunities and to be prepared for changes in employment trends in the context of blockchain innovations? Methodology. The study adopts exploratory multiple case analysis based on qualitative content analysis of job advertisement and expert interviews. Findings. The study develops a blockchain technology competence model for interdisciplinary academic and professional educational programs. The developed model can also be used for guiding the development of professional training, certification, and recruitment strategies and practice for blockchain projects.
Keywords: Blockchain technology; competence model; education; future jobs; interdisciplinarity; nascent technology